Behavioral health home impact on transitional care and readmissions among adults with serious mental illness. (29th October 2020) - Kennedy‐Hendricks, Alene; Bandara, Sachini; Daumit, Gail L.; Busch, Alisa B.; Stone, Elizabeth M.; Stuart, Elizabeth A.; Murphy, Karly A.; McGinty, Emma E.
Abstract: Objective: To evaluate the impact of Maryland's behavioral health homes (BHHs) on receipt of follow‐up care and readmissions following hospitalization among Medicaid enrollees with serious mental illness (SMI). Data Sources: Maryland Medicaid administrative claims for 12 232 individuals. Study Design: Weighted marginal structural models were estimated to account for time‐varying exposure to BHH enrollment and time‐varying confounders. These models compared changes over time in outcomes among BHH and comparison participants. Outcome measures included readmissions and follow‐up care within 7 and 30 days following hospitalization. Data Collection/Extraction Methods: Eligibility criteria included continuous enrollment in Medicaid for the first two years of the study period; 21‐64 years; and use of psychiatric rehabilitation services. Principal Findings: Over three years, BHH enrollment was associated with 3.8 percentage point (95% CI: 1.5, 6.1) increased probability of having a mental health follow‐up service within 7 days of discharge from a mental illness–related hospitalization and 1.9 percentage point (95% CI: 0.0, 3.9) increased probability of having a general medical follow‐up within 7 days of discharge from a somatic hospitalization. BHHs had no effect on probability of readmission. Conclusions: BHHs may improve follow‐up care for Medicaid enrollees with SMI, but effects do not translate into reduced risk of readmission.